SOSIALISASI SISTEM PEMBUMIAN PADA PENGEMBANGAN INSTALASI LISTRIK RUMAH TANGGA DI DESA PEKUTATAN JEMBRANA - Indra Partha C. Gd; W. Arta Wijaya; I N. Budiastra; AA . P. Raka Agung (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2011)
Villagers in the Pekutatan are not only relying on agricultural sector but also on industrial one. The industrial sector is home industrial scale such as coffee milling, flower, meat, and coconut grating. Almost all of this home industries use electricity as source of energy. At Pekutatan village, all of the sub-villages have been provided by electricity in which is not only used for lighting but also for improving productivity. It therefore increases the household income through this kind of industry. The development of electricity-based home industry in our society is not followed by sufficient understanding of electrical wiring practice. Many of the wiring installation is done without taking into account security and safety of the user. Therefore, lots of the residentials’ installation do not comply with the electrical installation code, PUIL 2000. This has led to risks of fire and electric shocks. In viewing this condition, the community service team from Department of Electrical Engineering Udayana University conducted seminar and demonstration of electrical wiring and grounding system in the selected villager’s home. Through this disemination we hope that the community will gain better understanding to protect themselves when carrying the tasks. The result of this activity was that the villagers of Pekutatan had attended seminar about electricicty system and grounding system, and taken part in workshop of electrical installation that follows PUIL 2000. In addition, a grounding system has been installed in Tempek Budi, Banjar Pasar Pekutatan and the system shows excellence performance.